The Validity and Clinical Utility of the COVERS Scale and Pain Assessment Tool for Assessing Pain in Neonates Admitted to an Intensive Care Unit. Issue 1 (January 2016) - O'Sullivan, Anna T.; Rowley, Simon; Ellis, Sharon; Faasse, Kate; Petrie, Keith J.
Abstract : Objectives: Infants admitted to a neonatal intensive care unit (NICU) are routinely subject to a range of painful procedures. However, pain assessments in NICUs are under-utilized due to a lack of a gold standard pain measure. In this study we assessed the psychometric properties and clinical utility of the COVERS and Pain Assessment Tool (PAT), in a neonatal unit. Methods: We had 72 nurses use the scales to assess pain at baseline and during a heel-lance procedure in 80 NICU infants. An independent research observer and the infant's mother also completed pain ratings. After the study, we assessed nurse preference and clinical utility ratings for both scales. Results: The COVERS had satisfactory internal consistency at baseline (Cronbach α=0.74) and heel lance (α=0.78), as did the PAT (baseline α=0.79, heel lance α=0.85). Intraclass correlation coefficients demonstrated good inter-rater reliability at baseline and heel lance, respectively, for both the COVERS (0.82 and 0.80) and the PAT (0.83 and 0.86). There were strong associations between total scores on the 2 scales at baseline ( r =0.81, P <0.001) and heel lance ( r =0.91, P <0.001), between researcher's ratings and total COVERS (ρ=0.75, P <0.001) and PAT scores (ρ=0.69, P <0.001), and between maternal ratings and total COVERS ( r =0.74, P <0.05) and PAT scores ( r =0.65, P <0.05). Both scales were sensitive to pain and nonpain events. Reliability and validity was mostly upheld across gestational age. Most nurses preferred the COVERS (52%) to the PAT (16%), and 32% had no preference. Discussion: This study builds on evidence for the COVERS scale and the PAT; both scales were reliable and valid measures of acute pain in neonates as premature as 24-week gestational age.